Perbaikan Administrasi di Kantor Desa Sebagai Implementasi Program KKN MBKM - Lukman Pakaya; Ayu Rakhma Wuryandini (Jurnal Pengabdian Dian Mandala, 2023)
The MBKM KKN program carried out by students is part of the successful implementation of the third tridharma of higher education. The aim of this additional program is to support village administrative facilities towards progress and modernization. The problem faced by partners is that partners still need administrative improvements in the form of improving financial file equipment, improving village documentation which is arranged using digital documentation and improving tax administration in the village. The methods used in this program are 1) in-depth observation, 2) interviews, 3) documentation, 4) technical guidance/mentoring. The results of this service to the community in Oluhuta village can be said to be that the program to improve village administrative facilities is progressing 85% in a positive direction for public service facilities. This program still needs to be continued considering the complexity of the tasks carried out by village officials and the need for continuous assistance.